The N270 as an index of consumer commodity color preference in the S1–S2 paradigm - Deming Shu; Deming Shu; Dianzhi Liu; Dianzhi Liu; Gong-Liang Zhang (Frontiers in Psychology, 2024)
IntroductionAffective decision-making is a prominent topic in consumer psychology research, with its core assumption being that consumers tend to purchase brands and commodities they like. However, the reasons behind why we develop emotional responses of liking or disliking toward certain commodities, as well as what the underlying neural mechanisms are, remain largely unknown.MethodsThis study utilized the S1–S2 paradigm in an experiment wherein S1 presented 12 types of commodities and S2 displayed 48 distinct colored squares. Participants were instructed to assess whether they “Like” or “Dislike” the commodity in S1, which was colored with the S2 color. Electroencephalogram (EEG) recordings were obtained during the reaction process and subsequently analyzed to examine the components of S2-induced event-related potentials (ERPs).ResultsThe analysis revealed that S2 elicited a significant N270 in the prefrontal scalp area under both the “Like” and “Dislike” conditions. Interestingly, the amplitude of the N270 was significantly higher during the “Dislike” condition compared to the “Like” condition.DiscussionThe N270 component was shown to reflect the conflict in physical attributes between S1 and S2, as well as the conflict between commodity and color. This highlights the potential utility of this component as an objective EEG indicator of consumer commodity color preferences in future marketing research.